Transformative Leadership in Education: Principal Leadership Styles and the Implementation of Merdeka Belajar Curriculum at School - Hasan, Azies; Fatiya, Asfa; Hrebatć, Mehmet (Islamic Educational Management Programme, 2024)
This study examines how school principals’ leadership styles on the implementation of the Merdeka Belajar program at MAN 1 Lombok. In an evolving educational landscape, transformational leadership is identified as a critical factor in facilitating positive and innovative changes in teaching and learning processes. Employing a qualitative case study design, this research utilized in-depth interviews and direct observations involving principals, teachers, and students. The research findings reveal that transformational leadership significantly influences the creation of a supportive learning environment that fosters student autonomy and creativity. Key determinants identified include effective communication, ongoing professional development for educators, and robust support for student initiatives. Despite these strengths, the study identifies notable challenges in the implementation of Merdeka Belajar, such as resistance to change and constraints related to resource availability. Consequently, this research underscores the necessity for leadership training for principals and advocates for enhanced collaboration among all educational stakeholders to ensure the program's successful execution. By elucidating the relationship between leadership styles and classroom practices, this study aims offers actionable insights to inform the development of more effective educational policies in Indonesia.